Pendampingan Branding Produk Lokal Berbasis Media Sosial bagi Pelaku Usaha Mikro di Gorontalo - Hamka Hamka; Asrul Asrul; Burhan Liputo; Wiwin S Makatutu (-, 2026)
The development of digital technology has created significant opportunities for micro-enterprises to expand their market reach through social media platforms. However, many micro-business owners in Gorontalo still lack an adequate understanding of effective digital branding strategies, causing local products to struggle in competing optimally in the market. This community service activity aimed to improve the capacity of micro-enterprise owners in building brand identity, creating promotional content, and utilizing social media as a digital marketing tool. The implementation methods included observation, training, mentoring, and evaluation for micro-business actors in Gorontalo. The results showed an increase in participants’ understanding of product branding, the use of social media for promotion, and the ability to create more attractive and communicative marketing content. In addition, business owners began independently applying digital marketing strategies through social media platforms such as Instagram, Facebook, and TikTok. This activity is expected to enhance the competitiveness of local products and support sustainable community economic growth.